揭開日本學生傑出表現背後的秘密：教學研究 The Most Significant Factor Underlying Japanese Students' Academic Success: Lesson Study - 黃源河Yuanher Robin Hwang; 符碧真 Bih-Jen Fwu (National Taiwan Normal University, 2011)
1995年日本中小學生在國際數理競賽（Trends in International Mathematics and Science Study, TIMSS）傲人的表現，引發國際學者的好奇，紛紛探究其背後的原因。結果發現，日本教師專業發展模式──「教學研究」居功厥偉。雖然最近兩次國際數理競賽，日本學生的表現略微下滑，但其實施近百年，頗具特色的「教學研究」仍值得各國關注。本研究旨在探討日本的教學研究如何聚焦於學生學習，以增進教師專業成長。全文先介紹日本的課堂教學，其次說明其幕後推手「教學研究」，並舉出運作實例，接著進行學理分析，最後討論對我國師資培育與中小學教育的啟示。 The outstanding performance of Japanese students in the Trends in International Mathematics and Science Study (TIMSS) in 1995 attracted significant international attention. Numerous education researchers have attempted to determine what factors or practices underlie Japanese students' success. They found that lesson study, a specialized model of teacher professional development used in Japan for over 100 years, can be credited with significant contributions to the improvement of instructional practices, resulting in excellent student performance and academic achievement. This study investigates how lesson study furthers teacher professional development and improves student learning, and examines and analyzes the underlying rationale. Finally, we present the practical implications of this investigation and analysis to inform current discussions on education and teacher professional development in Taiwan.